Anti-moisture and anti-layering optical composite film and preparation method thereof
By using copper roller transfer technology to engrave the prism structure and the wall-like blank structure in the optical composite film, an optical composite film with sealed prism structure is formed, which solves the problems of water vapor intrusion and layering, and achieves efficient waterproof and peel resistance.
Patent Information
- Application Number
- CN202411906772.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
Smart Images

Figure BDA0005204560090000091 
Figure BDA0005204560090000101 
Figure HDA0005204560100000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical films, and in particular to a method for preparing an optical composite film with a sealed prism structure. Background Art
[0002] Optical composite film is a composite thin film material with multiple optical functions, which is widely used in display, lighting, solar cell and other fields. my country is a country with a large production capacity of optical films, and the optical films produced are shipped to all parts of the world by sea, land and air. In a complex transportation and use environment, humidity and temperature change frequently, which can easily lead to deformation of the film, water vapor intrusion and other problems, affecting the appearance and optical properties of the film surface. In addition, optical composite films are prone to delamination, that is, peeling occurs between the film layer and the substrate or within the film layer, which seriously affects its optical properties and service life. Therefore, improving the stability of optical composite films is a technical problem that needs to be solved urgently, among which water vapor resistance and anti-delamination have become important development directions.
[0003] The waterproof function can ensure that the optical film maintains good performance in a humid environment, greatly improving the scope of application and practicality of the optical film. Traditional waterproof vapor-proof technologies include water-combing modification of optical film materials (CN107226920A), filling glue on the surface of the structural layer (CN219435175U), edge hot melt adhesive sealing (CN213817855U), edge bonding barrier film to wrap the composite film (CN214278462U), display panel waterproof structure design (CN113066932A), etc., which have certain waterproof functions. However, the cost of material modification and filling glue is high, the edge sealing of the optical film increases the difficulty of cutting and assembly operations, and the display panel waterproof design cannot prevent water vapor intrusion before the membrane is assembled, all of which have certain limitations.
[0004] Anti-delamination can improve the yield of the film during production, cutting and assembly. Especially during the cutting process, due to the stiffness of the upper and lower substrates of the optical composite film, cutting and peeling delamination are prone to occur. The current anti-delamination technology for optical composite films includes the development of high-strength adhesives (CN110776837A), and improving the peeling force by changing the internal structure of the composite film (CN214774584U), which have played a certain anti-delamination role. However, the cost of adhesive modification is expensive and the process is cumbersome; conventional improvements in the internal structure of composite films will affect the optical properties. Therefore, it is crucial to take into account the mechanical strength, environmental stability, optical properties and manufacturing costs of the film layer and achieve a balance of multiple properties. Summary of the invention
[0005] In order to solve the problems of water vapor intrusion and easy delamination of an optical composite film, the present invention provides a structural design of an optical composite film and a preparation method thereof.
[0006] To achieve the above-mentioned purpose, the present invention first provides an optical composite film that is waterproof and anti-delamination, including a back coating layer, a lower substrate, a first structural molding layer, a bonding layer, an upper substrate, and a second structural molding layer arranged in sequence from bottom to top; wherein the first structural molding layer is transferred by a copper roller, and a circle of wall-like blank structure is engraved on the copper roller to transfer it into a first structural molding layer with a surrounding wall structure; the first structural molding layer transferred by the copper roller and the upper substrate are bonded by using a bonding layer, and then the second structural molding layer is prepared on the upper substrate, so as to obtain a sealed optical composite film with dual functions of waterproof vapor intrusion and anti-delamination.
[0007] Preferably, the particles of the back coating layer are one or more of polymethyl methacrylate (PMMA), polyurethane (PU), polybutyl methacrylate (PBMA), polyamide (PA) and polystyrene (PS).
[0008] Preferably, the thickness of the back coating layer is 3-7 μm, or 4 μm, 5 μm, or 6 μm.
[0009] Preferably, the glue of the back coating layer, the glue of the first structure forming layer, the glue of the second structure forming layer and the glue of the laminating layer are modified acrylic resins.
[0010] Preferably, the thickness of the lower substrate and the upper substrate is 50-250 μm, or 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, or 220 μm.
[0011] Preferably, the material of the lower substrate and the upper substrate is one or more of polyethylene terephthalate (PET), polycarbonate (PC) and polystyrene (PS).
[0012] Preferably, the structure of the middle area of the first structural forming layer is prism-shaped.
[0013] Preferably, the structure of the prisms in the middle area of the first structural forming layer is one or more of an equal-height structure, a one-high-one-low cycle structure, and a one-high-two-low cycle structure.
[0014] Preferably, the pitch of the prisms in the middle area of the first structural molding layer is 0-100 μm, or 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 70 μm, or 90 μm.
[0015] Preferably, the angle between the prism in the middle area of the first structural forming layer and the long side of the diaphragm is 0-90°, or 2°, 10°, 20°, 30°, 50°, 80°, or 85°.
[0016] Preferably, the cross-section of the surrounding wall structure of the first structural forming layer is one or more of a rectangle, a right-angled trapezoid, an isosceles trapezoid, and a semicircle with a chord cut off.
[0017] Preferably, the cross-section of the blank structure around the copper roller is one or more of a rectangle, an inverted right-angle trapezoid, an inverted isosceles trapezoid, and an inverted semicircle with a chord cut off. Such a structure can be demoulded better.
[0018] Preferably, the cross-sectional width of the blank structure is 5 mm to 10 mm, or 6 mm, 7 mm, 8 mm, or 9 mm.
[0019] Preferably, the depth of the blank structure is consistent with the prism depth.
[0020] Preferably, the thickness of the bonding layer is 0.1-2 μm, or 0.2 μm, 0.5 μm, 0.8 μm, 1.0 μm, or 1.5 μm.
[0021] Preferably, the structure of the second structural forming layer is one of a microlens hemispherical shape (prepared into a microlens composite prism film-MOP), a prism shape (prepared into a prism composite prism film-POP) and a diffusion shape (prepared into a diffusion composite prism film-DOP).
[0022] The present invention also provides a method for preparing a water vapor and anti-delamination optical composite film, wherein the optical composite film comprises a back coating layer, a lower substrate, a first structural forming layer, a laminating layer, an upper substrate, and a second structural forming layer which are arranged in sequence, and comprises the following steps:
[0023] Step (1), preparing a copper roller structure for transferring the first structure forming layer, engraving an inverted prism structure in the central area of the copper roller, and engraving a wall-like blank structure around the central area;
[0024] Step (2), using back-coating particles and back-coating glue to prepare a back-coating layer, and applying the back-coating layer on the lower substrate;
[0025] Step (3), transferring the first structure forming layer onto the lower substrate by means of a copper roller using the first structure forming layer glue;
[0026] Step (4), using a laminating layer glue to prepare a laminating layer, and laminating the first structure forming layer and the upper substrate;
[0027] Step (5), preparing a second structural forming layer on the upper substrate.
[0028] Preferably, the particles of the back coating layer are one or more of polymethyl methacrylate (PMMA), polyurethane (PU), polybutyl methacrylate (PBMA), polyamide (PA) and polystyrene (PS).
[0029] Preferably, the thickness of the back coating layer is 3-7 μm, or 4 μm, 5 μm, or 6 μm.
[0030] Preferably, the back coating glue, the first structure forming layer glue, the second structure forming layer glue and the laminating layer glue are modified acrylic resins.
[0031] Preferably, the thickness of the lower substrate and the upper substrate is 50-250 μm, or 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, or 220 μm.
[0032] Preferably, the material of the lower substrate and the upper substrate is one or more of polyethylene terephthalate (PET), polycarbonate (PC) and polystyrene (PS).
[0033] Preferably, the structure of the middle area of the first structural forming layer is prism-shaped.
[0034] Preferably, the structure of the prisms in the middle area of the first structural forming layer is one or more of an equal-height structure, a one-high-one-low cycle structure, and a one-high-two-low cycle structure.
[0035] Preferably, the pitch of the prisms in the middle area of the first structural molding layer is 0-100 μm, or 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 70 μm, or 90 μm.
[0036] Preferably, the angle between the prism in the middle area of the first structural forming layer and the long side of the diaphragm is 0-90°, or 2°, 10°, 20°, 30°, 50°, 80°, or 85°.
[0037] Preferably, the cross-section of the surrounding wall structure of the first structural forming layer is one or more of a rectangle, a right-angled trapezoid, an isosceles trapezoid, and a semicircle with a chord cut off.
[0038] Preferably, the cross-section of the blank structure around the copper roller is one or more of a rectangle, an inverted right-angle trapezoid, an inverted isosceles trapezoid, and an inverted semicircle with a chord cut off. Such a structure can be demoulded better.
[0039] Preferably, the cross-sectional width of the blank structure is 5 mm to 10 mm, or 6 mm, 7 mm, 8 mm, or 9 mm.
[0040] Preferably, the depth of the blank structure is consistent with the prism depth.
[0041] Preferably, the thickness of the bonding layer is 0.1-2 μm, or 0.2 μm, 0.5 μm, 0.8 μm, 1.0 μm, or 1.5 μm.
[0042] Preferably, the structure of the second structural forming layer is one of a microlens hemispherical shape (prepared into a microlens composite prism film-MOP), a prism shape (prepared into a prism composite prism film-POP) and a diffusion shape (prepared into a diffusion composite prism film-DOP).
[0043] The present invention also provides an application of a copper roller structure in improving the performance of an optical film, wherein the copper roller structure is a reverse prism structure engraved in the central area of the copper roller, and a wall-like blank structure is engraved around the central area; the optical composite film comprises a back coating layer, a lower substrate, a first structural molding layer, a bonding layer, an upper substrate, and a second structural molding layer arranged in sequence; the optical film has waterproof vapor resistance and anti-delamination properties.
[0044] Preferably, the optical film has the following properties: no water ingress at high temperature and high humidity (85° C. / 85%) for 1000 hours, and a peeling force greater than 300 gf.
[0045] Compared with the prior art, the product provided by the present invention has the following advantages or functions:
[0046] (1) There is no need to modify the material. Compared with MOP, POP and DOP produced by normal process, the basic optical and physical properties such as brightness, haze, transmittance and physical strength of the optical composite film produced do not change, and the cost is low.
[0047] (2) Compared with conventional optical films that use hot melt adhesive edge sealing technology, the optical composite film has an additional feature of controllable effective width and effective length. In addition, the optical composite film has waterproof and anti-delamination functions as soon as it is prepared. After testing, it will not get wet for 1000 hours at high temperature and high humidity (85℃ / 85%), and the peeling force is greater than 300gf (GB / T 2792-2014), which is convenient for transportation, cutting and assembly.
[0048] (3) The preparation method is simple, and only requires carving out a portion of the copper roller structure, which will not increase the process flow. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a photo of a copper roller according to an embodiment of the present invention.
[0050] Figure 2 A three-dimensional schematic diagram of a copper roller with a blank rectangular cross-section according to an embodiment of the present invention.
[0051] Figure 3 It is a front view schematic diagram of a copper roller with a blank rectangular cross-section according to an embodiment of the present invention.
[0052] Figure 4 It is a side schematic diagram of a copper roller with a blank rectangular cross-section according to an embodiment of the present invention.
[0053] Figure 5 This is a photo of the MOP of an embodiment of the present invention.
[0054] Figure 6 It is a three-dimensional schematic diagram of the lower substrate and the first structural forming layer (with rectangular cross sections all around) of the optical composite film according to an embodiment of the present invention.
[0055] Figure 7 It is a front view schematic diagram of the MOP optical composite film according to an embodiment of the present invention.
[0056] Figure 8 Schematic side view of the MOP optical composite film according to an embodiment of the present invention.
[0057] Fig. 9 It is a front view schematic diagram of a POP optical composite film according to an embodiment of the present invention.
[0058] Fig.10 It is a side schematic diagram of a POP optical composite film according to an embodiment of the present invention.
[0059] Fig.11 It is a front view schematic diagram of a DOP optical composite film according to an embodiment of the present invention.
[0060] Fig.12 It is a side schematic diagram of the DOP optical composite film according to an embodiment of the present invention.
[0061] Fig.13 It is a three-dimensional schematic diagram of a blank copper roller with an inverted right-angled trapezoidal cross-section according to an embodiment of the present invention.
[0062] Fig.14 It is a three-dimensional schematic diagram of the lower substrate and the first structural forming layer (with right-angled trapezoidal cross sections all around) of the optical composite film according to an embodiment of the present invention.
[0063] Fig.15 A three-dimensional schematic diagram of a blank copper roller with an inverted isosceles trapezoidal cross-section according to an embodiment of the present invention.
[0064] Fig.16 It is a three-dimensional schematic diagram of the lower substrate and the first structural forming layer (with isosceles trapezoidal cross-sections all around) of the optical composite film according to an embodiment of the present invention.
[0065] Fig.17 A three-dimensional schematic diagram of a blank copper roller with a semicircular cross-section with a chord cut away according to an embodiment of the present invention.
[0066] Fig.18 It is a three-dimensional schematic diagram of the lower substrate and the first structural forming layer (surrounded by a semicircular cross section with a chord cut off) of the optical composite film according to an embodiment of the present invention. DETAILED DESCRIPTION
[0067] In order to more clearly illustrate the technical solutions in the present invention, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0068] The relevant performance test methods include: 1. Peel force test: According to GB / T 2792-2014 standard, cut a 25mm wide composite film for testing. 2. Water vapor test: Put the film into a high temperature and high humidity box (85℃ / 85%) for 1000 hours, take it out, and observe the film with the naked eye for water vapor intrusion. 3. Brightness gain test: Cut each embodiment and comparative example into films of the same size, place them in the Hisense 65E3H.T.B2 display, and use a handheld brightness meter to perform brightness test.
[0069] Example 1
[0070] A sealed MOP optical composite film with dual functions of water vapor intrusion prevention and anti-delamination ( Figure 5 ) is prepared as follows:
[0071] Step (1), preparing a copper roller structure for transferring the first structure forming layer, such as Figures 1 to 4 As shown, first, a reverse prism structure is engraved in the center area of the copper roller, which is equivalent to the effective area of the application end of the composite film, and then a circle of wall-like blank structure is engraved around the center area of the copper roller. The cross section is a rectangle that is easier to demould, the width is 10mm, and the depth is consistent with the prism depth;
[0072] Step (1), using back-coating particles and back-coating glue to prepare a back-coating layer with a thickness of 5 μm, and applying it on a lower PET substrate with a thickness of 125 μm;
[0073] Step (3), using a copper roller to transfer the first structure forming layer glue to the lower substrate to form the first structure forming layer, wherein the central structure is a prism shape, the pitch is 70 μm with the same height, the angle between the prism and the long side of the membrane is 0°, and the surrounding is a rectangular cross-section wall structure ( Figure 6 );
[0074] Step (4), using adhesive to make a 1 μm thick laminating layer, the first structure forming layer and the 125 μm thick upper PET substrate are bonded. Above the transferred prism, the blank inverted triangle structure is filled and blocked, and after being tightly attached to the upper substrate, water vapor can be prevented from entering the composite film through the blank channel above the prism, and has an ultra-wide laminating contact surface greater than 5 mm, thereby having an ultra-high peeling force of more than 300 gf;
[0075] Step (5), using modified acrylic resin to form a second structure forming layer ( Figure 7 and Figure 8 ).
[0076] The whole prepared above is a sealed MOP optical composite film with dual functions of preventing water vapor intrusion and resisting delamination.
[0077] Example 2
[0078] The difference from Example 1 is that it is a method for preparing a sealed POP optical composite film with dual functions of water vapor intrusion and anti-delamination. A prism-shaped second structural molding layer ( Fig. 9 and Fig.10 ). The prepared whole is a sealed POP optical composite film with dual functions of preventing water vapor intrusion and anti-delamination.
[0079] Example 3
[0080] The difference from Example 1 is that it is a method for preparing a sealed DOP optical composite film with dual functions of water vapor intrusion and anti-delamination. A second structural forming layer ( Fig.11 and Fig.12 The whole is a sealed DOP optical composite film with dual functions of preventing water vapor intrusion and anti-delamination.
[0081] Example 4
[0082] The difference from Example 1 is that a circle of blank structure in the shape of a wall is carved around the central area of the copper roller, and its cross section is an inverted right-angled trapezoid ( Fig.13 ), its width is 10mm and its depth is consistent with the prism depth.
[0083] The first structure molding layer is transferred using the first structure molding layer glue, the central structure of which is a prism, the pitch is 70μm with the same height, the angle between the prism and the long side of the membrane is 0°, and the surrounding wall structure is a right-angle trapezoidal cross-section ( Fig.14 ).
[0084] Example 5
[0085] The difference from Example 1 is that a circle of blank structure in the shape of a wall is carved around the central area of the copper roller, and its cross section is an inverted isosceles trapezoid ( Fig.15 ), its width is 10mm and its depth is consistent with the prism depth.
[0086] The first structure molding layer is transferred using the first structure molding layer glue, the central structure of which is a prism, the pitch is 70μm with the same height, the angle between the prism and the long side of the membrane is 0°, and the surrounding wall structure is an isosceles trapezoidal cross-section ( Fig.16 ).
[0087] Example 6
[0088] The difference from Example 1 is that a circle of blank structure in the shape of a wall is carved around the central area of the copper roller, and its cross section is a semicircle with a chord cut off, which is easier to demould ( Fig.17 ), its width is 10mm and its depth is consistent with the prism depth.
[0089] The first structure molding layer is transferred using the first structure molding layer glue, the central structure of which is a prism shape, the pitch is 70μm with the same height, the angle between the prism and the long side of the membrane is 0°, and the surrounding is a wall structure with a semicircular cross-section cut off a chord ( Fig.18 ).
[0090] Table 1 Comparison of optical composite film performance and cost
[0091]
[0092]
[0093] Comparative Example 1
[0094] Comparative Example 1 is a mass-produced MOP finished product on the market. The difference from Example 1 is that there is no blank structure around the central area of the copper roller, the width is 10 mm, and the depth is consistent with the prism depth.
[0095] The first structure molding layer is transferred using the first structure molding layer glue, wherein the central structure is a prism shape, the pitch is 70 μm with the same height, the angle between the prism and the long side of the membrane is 0°, and there is no surrounding wall structure.
[0096] Comparative Example 2
[0097] The barrier film sealing treatment is performed on Comparative Example 1 using the CN214278462U technology. The treatment method is as follows: the multilayer optical bonding film with an edge sealing structure includes a multilayer optical film, an edge sealing portion arranged along the edge of the optical bonding film and capable of encapsulating the edge of each layer of the optical film, the edge sealing portion includes a barrier film, and the barrier film is bonded to the edge of the multilayer optical bonding film by epoxy resin adhesive.
[0098] Comparative Example 3
[0099] The prism layer is filled and coated with a flat layer on the comparative example 1 using the CN219435175U technology. The processing method is as follows: a flat coating layer is provided on the side of the first structural layer away from the substrate layer, and the flat coating layer fills and covers the surface of the first structural layer. The flat coating layer is uniformly filled and coated with acrylic resin on the surface of the first structural layer by the micro-concave anilox roller and the doctor blade coating process of the precision coating machine. By controlling the linear speed ratio of the micro-concave anilox roller, the surface height of the flat coating layer is made higher than the top of the first structural layer structure, and is cured by UV ultraviolet radiation. By filling and covering the surface of the first prism array with a flat coating layer, and then providing a lens array on the surface of the flat coating layer, the effect of multiple structures fitting each other on a single substrate layer can be achieved.
[0100] It can be concluded from the test results of the above embodiments and comparative examples that the waterproof and anti-delamination optical composite film provided by the present invention has multiple advantages such as low cost, high brightness, high peeling force, high waterproofness, and better comprehensive performance.
[0101] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.
Claims
1. A water vapor and anti-delamination optical composite film, comprising a back coating, a lower substrate, a first structure forming layer, a bonding layer, an upper substrate, and a second structure forming layer arranged in sequence from bottom to top; wherein the first structure forming layer is transferred by a copper roller, and a circle of wall-like blank structure is engraved on the copper roller to transfer the first structure forming layer having a surrounding wall structure; the first structure forming layer transferred by the copper roller and the upper substrate are bonded by using the bonding layer, and then the second structure forming layer is prepared on the upper substrate, so as to obtain a sealed optical composite film with dual functions of water vapor intrusion and anti-delamination.
2. The optical composite film according to claim 1, characterized in that: The particles of the back coating layer are one or more of polymethyl methacrylate (PMMA), polyurethane (PU), polybutyl methacrylate (PBMA), polyamide (PA) and polystyrene (PS).
3. The optical composite film according to claim 1, characterized in that: The thickness of the back coating layer is 3-7 μm.
4. The optical composite film according to claim 1, characterized in that: The glue of the back coating layer, the glue of the first structure forming layer, the glue of the second structure forming layer and the glue of the laminating layer are modified acrylic resin.
5. The optical composite film according to claim 1, characterized in that: The thickness of the lower substrate and the upper substrate is 50-250 μm.
6. The optical composite film according to claim 1, characterized in that: The material of the lower substrate and the upper substrate is one or more of polyethylene terephthalate (PET), polycarbonate (PC) and polystyrene (PS).
7. The method for preparing an optical composite film according to any one of claims 1 to 6, wherein the optical composite film comprises a back coating layer, a lower substrate, a first structural forming layer, a bonding layer, an upper substrate, and a second structural forming layer arranged in sequence, comprising the following steps: Step (1), preparing a copper roller structure for transferring the first structure forming layer, engraving an inverted prism structure in the central area of the copper roller, and engraving a wall-like blank structure around the central area; Step (2), using back-coating particles and back-coating glue to prepare a back-coating layer, and applying the back-coating layer on the lower substrate; Step (3), transferring the first structure forming layer onto the lower substrate by means of a copper roller using the first structure forming layer glue; Step (4), using a laminating layer glue to prepare a laminating layer, and laminating the first structure forming layer and the upper substrate; Step (5), preparing a second structural forming layer on the upper substrate.
8. The method for preparing an optical composite film according to claim 7, characterized in that: The structure of the middle area of the first structural molding layer is prism-shaped.
9. The method for preparing an optical composite film according to claim 7, characterized in that: The structure of the prisms in the middle area of the first structural forming layer is one or more of an equal height structure, a one-high-one-low cycle structure, and a one-high-two-low cycle structure.
10. The method for preparing an optical composite film according to claim 7, characterized in that: The pitch of the prisms in the middle area of the first structural molding layer is 0-100 μm.
11. The method for preparing an optical composite film according to claim 7, characterized in that: The included angle between the prism in the middle area of the first structure forming layer and the long side of the membrane is 0-90 degrees.
12. The method for preparing an optical composite film according to claim 7, characterized in that: The cross-section of the surrounding wall structure of the first structural forming layer is one or more of a rectangle, a right-angled trapezoid, an isosceles trapezoid, and a semicircle with a chord cut off.
13. The method for preparing an optical composite film according to claim 7, characterized in that: The cross section of the blank structure around the copper roller is one or more of a rectangle, an inverted right-angled trapezoid, an inverted isosceles trapezoid, and an inverted semicircle with a chord cut off.
14. The method for preparing an optical composite film according to claim 13, characterized in that: The cross-sectional width of the blank structure is 5 mm to 10 mm.
15. The method for preparing an optical composite film according to claim 13, characterized in that: The depth of the blank structure is consistent with the prism depth.
16. The method for preparing an optical composite film according to claim 7, characterized in that: The thickness of the laminating layer is 0.1-2 μm.
17. The method for preparing an optical composite film according to claim 7, characterized in that: The structure of the second structural molding layer is one of a microlens hemispherical shape (prepared into a microlens composite prism film-MOP), a prism shape (prepared into a prism composite prism film-POP) and a diffusion shape (prepared into a diffusion composite prism film-DOP).
18. The method for preparing an optical composite film according to claim 7, characterized in that: 。 19. An application of a copper roller structure in improving the performance of an optical film, wherein the copper roller structure is a reverse prism structure engraved in the central area of the copper roller, and a wall-like blank structure is engraved around the central area; the optical composite film includes a back coating layer, a lower substrate, a first structural molding layer, a bonding layer, an upper substrate, and a second structural molding layer arranged in sequence; the optical film has waterproof and anti-delamination properties.
20. The use according to claim 19, characterized in that The optical film has the following properties: no water ingress at high temperature and high humidity (85° C. / 85%) for 1000 hours, and a peeling force greater than 300 gf.
Citation Information
Patent Citations
Preparation method of photocuring type superhydrophobic composite film
CN107226920A
Light-transmitting barrier composite film and preparation method thereof
CN110776837A
Display device, display panel and manufacturing method of display panel
CN113066932A
Mobile phone liquid crystal display screen with novel sealing waterproof structure
CN213817855U
Optical composite film capable of improving productivity and stripping effect
CN214774584U